Premenstrual syndrome: new insights into etiology and review of treatment methods - Modzelewski, Stefan; Oracz, Aleksandra; Żukow, Xawery; Iłendo, Kamila; Śledzikowka, Zofia; Waszkiewicz, Napoleon (Frontiers in Psychiatry, 2024)
Premenstrual syndrome (PMS) is a common disorder affecting women of reproductive age, with an estimated global prevalence of 47.8%, with severe symptoms occurring in 3-8%, significantly affecting daily functioning. GABA conductance and changes in neurosteroid levels, particularly allopregnanolone, are suspected to play a substantial role in the disorder's etiology. In this paper, we provide an overview of recent reports on the etiology and recognized therapeutic approaches, encompassing both pharmacological and non-pharmacological interventions. Our examination includes studies on SSRIs, hormonal agents, neurosteroids, supplementation, and therapeutic roles. We aim to determine the most favorable treatment regimen by comparing medication effects and alternative methods. The treatment of PMS is crucial for enhancing the quality of life for affected women. Medications used in PMS treatment should be individually selected to achieve the best therapeutic effect, considering the clinical situation of the patients.